Yoga, singing, and the singer: a balance of effort and ease - McCornack, Heather (Kansas State University, 2021)
This report explores how the practice of yoga can support singing and the singer. Through the actions of movement, proprioception, exteroception and interoception, yoga can improve body awareness and provide accessibility to a full, expansive breath. These combined skills can produce a healthy and consistent tone upon which a singer can depend and succeed. In addition to physical benefits, yoga can provide psychological and emotional support. This is accomplished through breathwork that balances the nervous system and allows singers to flourish under the many stressors of a performance or teaching career. This report will explain how and why incorporating a yoga practice into voice work and teaching is wholly beneficial.
Keywords: Yoga; Singing; Embodiment; Singer